2016
DOI: 10.1681/asn.2014121228
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mg2+ Reabsorption and Transient Receptor Potential Melastatin Type 6 Activity by cAMP Signaling

Abstract: ABSTRACTsurface biotinylation, and total internal reflection fluorescence live cell imaging of transfected HEK293 cells, we demonstrated that cAMP signaling rapidly potentiates TRPM6 activity by promoting TRPM6 accumulation at the plasma membrane and increasing its single-channel conductance. Comparison of electrophysiological data from cells expressing the phosphorylation-deficient S1252A or phosphomimetic S1252D TRPM6 mutants suggests that phosphorylation at this intracellular residue participates in the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…The mechanisms by which mutations in TRPM6 lead to HSH are unknown, although several studies stress the importance of TRPM6-mediated Mg 2+ conductance (3)(4)(5). Importantly, global TRPM6 disruption in mice is embryonic lethal (6,7).…”
Section: For a Recent Review)mentioning
confidence: 99%
“…The mechanisms by which mutations in TRPM6 lead to HSH are unknown, although several studies stress the importance of TRPM6-mediated Mg 2+ conductance (3)(4)(5). Importantly, global TRPM6 disruption in mice is embryonic lethal (6,7).…”
Section: For a Recent Review)mentioning
confidence: 99%
“…Recent studies have shown that plasma membrane TRPM6 expression can be stimulated by the adenylyl cyclase 3 (AC3)/ cAMP/PKA-mediated signaling pathway. AC3 is also colocalized with Na-Cl cotransporter (NCC) in the DCL [49] . In mice with kidney-specific AC3 knockout, urine Mg 2+ wasting, hypomagnesemia when on a low-Mg 2+ diet, colocalization of AC3 and NCC, and activation of cAMP-PKA with increasing apical membrane expression and channel conductance of TRPM6 have all been demonstrated [49] .…”
Section: Trpm6mentioning
confidence: 99%
“…AC3 is also colocalized with Na-Cl cotransporter (NCC) in the DCL [49] . In mice with kidney-specific AC3 knockout, urine Mg 2+ wasting, hypomagnesemia when on a low-Mg 2+ diet, colocalization of AC3 and NCC, and activation of cAMP-PKA with increasing apical membrane expression and channel conductance of TRPM6 have all been demonstrated [49] . Schematic presentation of magnesium regulation in the distal convoluted tubule.…”
Section: Trpm6mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, cisplatin downregulates the EGF and TRPM6 mRNA levels and increases the fractional excretion Mg 2+ , suggesting that cisplatin treatment results in a diminished renal Mg 2+ reabsorption via TRPM6 [92]. Adenylyl Cyclase 3 (AC3)-PKA signaling pathway A also increases TRPM6 abundance at the apical plasma membrane and channel activity, but the upstream extracellular signal was not defined [93]. In addition to hormonal control, renal TRPM6 expression is under control of other systemic factors.…”
Section: Introductionmentioning
confidence: 99%